Coating of DNA/poly(L-lysine) complexes by covalent attachment of poly[N-(2-hydroxypropyl)methacrylamide] - Subr, Vladimír; Konák, Cestmír; Laga, Richard; Ulbrich, Karel (Biomacromolecules, 2006)
N-(2-Hydroxypropyl)methacrylamide (HPMA) copolymers (pHPMA) containing 4-nitrophenyl ester (ONp) or thiazolidine-2-thione (TT) reactive groups in side chains and telechelic/semitelechelic pHPMA with TT groups were designed as highly hydrophilic biocompatible polymers suitable for chemical coating of polyelectrolyte-based DNA-containing nanoparticles bearing amino groups on the surface. The course of the coating reaction carried out in aqueous solution was evaluated on model self-assembling polyelectrolyte DNA/poly(L-lysine) (DNA/PLL) complexes either by monitoring the amount of residual polymer reactive groups by UV spectroscopy or by monitoring changes in the weight-average molecular weight and hydrodynamic size of the complexes using light scattering methods. Physicochemical stability of the coated complexes in buffered saline solution was also investigated. Contrary to uncoated particles, the coated complexes showed remarkable stability to aggregate in 0.15 M NaCl. Coating with pHPMA had practically no effect on the size distribution of the most stable complexes prepared by complexation of DNA with high-molecular-weight PLL (M(w) = 134 000) as shown by dynamic light scattering. The coating reaction was faster and more efficient with multivalent HPMA copolymers containing TT reactive groups than that with HPMA copolymers containing ONp groups.
Keywords: Hydrolysis; Thiazolidines; Nitrobenzenes; hydrolýza; molekulová hmotnost; Spectrophotometry, Ultraviolet; chlorid sodný; molekulární struktura; nitrobenzeny; Polylysine; Molecular Structure; DNA; polylysin; Amination; Kinetics; thiazoly; Polymethacrylic Acids; thiazolidiny; aminace; spektrofotometrie ultrafialová; Thiazoles; Sodium Chloride; kyseliny polymethakrylové; kinetika; Molecular Weight